Menolak Tunduk - Aprianita, Triana; Wahyudi, Johan (The International Journal of Pegon : Islam Nusantara civilization, 2024)
This article examines the existence of Tawan Karang Rights as one of the traditional legal practices in the archipelago which was maintained by the coastal communities of the Dutch East Indies until the end of the 19th century. The focus of this research is to understand how Tawan Karang Rights as a form of customary law interact, conflict and negotiate with the international shipping legal framework introduced by the Dutch colonial era. This research uses legal research methods by looking at the legal products of Tawan Karang in the Kingdom of Bali and the Kingdom of Teunom, in Aceh and comparing them with conventional shipping law at that time. This article shows that the interaction between Tawan Karang Rights and international shipping law in the Dutch East Indies was a reflection of the broader conflict between customary law and colonial law. This practice not only reflects the socio-economic dynamics of coastal communities, but also highlights how customary law attempts to negotiate its existence in the face of modern legal pressures brought about by colonialism. Artikel ini mengkaji keberadaan Hak Tawan Karang sebagai salah satu praktik hukum tradisional di Nusantara yang dipertahankan oleh masyarakat pesisir Hindia Belanda hingga akhir abad ke-19. Fokus penelitian ini adalah memahami bagaimana Hak Tawan Karang sebagai bentuk hukum adat berinteraksi, berkonflik, dan bernegosiasi dengan kerangka hukum pelayaran internasional yang diperkenalkan oleh kolonial Belanda. Penelitian ini menggunakan metode penelitian hukum dengan melihat produk hukum Tawan karang di Kerajaan Bali dan Kerajaan Teunom, di Aceh dan mengkomparasikannya dengan hukum pelayaran konvensional kala itu. Artikel ini menunjukkan bahwa interaksi antara Hak Tawan Karang dan hukum pelayaran internasional di Hindia Belanda merupakan cerminan dari konflik yang lebih luas antara hukum adat dan hukum kolonial. Praktik ini tidak hanya mencerminkan dinamika sosial-ekonomi masyarakat pesisir, tetapi juga menyoroti bagaimana hukum adat berupaya menegosiasikan keberadaannya dalam menghadapi tekanan hukum modern yang dibawa oleh kolonialisme.